2021
DOI: 10.4236/jss.2021.91021
|View full text |Cite
|
Sign up to set email alerts
|

A Fall from Grace: An Interpretative Phenomenological Analysis of Unemployment in UK University Graduates with Common Mental Health Issues

Abstract: An exploratory investigation into the experiences of unemployed university graduates with common mental health issues (i.e., depression and anxiety) was conducted using Interpretative Phenomenological Analysis. Analysis of semi-structured interviews with 12 graduates in their twenties, all of whom had been unemployed between five and 24 months with common mental health issues, generated themes relating to "Loss of Expectation and Disorientation", "Waste, Failure and Blame", and "Stigma and Shame". Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Mental health was negatively impacted by the socially constructed meaning of a valuable, accepted member of society as someone who is, above all else, making an economic contribution. This builds on other qualitative findings that without work, people feel excluded from society [ 28 , 32 , 34 ]. It was not the implication that participants needed to find paid work that was harmful in itself (indeed, this was typically participants’ primary goal), but rather the sense of a prevailing societal attitude that portrayed anyone not in paid work for a period of time as deviant, even when this is outside of their control.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Mental health was negatively impacted by the socially constructed meaning of a valuable, accepted member of society as someone who is, above all else, making an economic contribution. This builds on other qualitative findings that without work, people feel excluded from society [ 28 , 32 , 34 ]. It was not the implication that participants needed to find paid work that was harmful in itself (indeed, this was typically participants’ primary goal), but rather the sense of a prevailing societal attitude that portrayed anyone not in paid work for a period of time as deviant, even when this is outside of their control.…”
Section: Discussionsupporting
confidence: 67%
“…To date, much of the qualitative literature in this area has focused on how unemployment is experienced by those with severe mental health issues [27][28][29][30][31] and other specific subgroups (e.g. age groups, genders or durations of unemployment [32][33][34][35][36][37]).…”
Section: Introductionmentioning
confidence: 99%
“…Among the many psychological responses to unemployment seen in young graduates, we highlight disorientation, a sense of injustice as they expected good career prospects, and the stigma of unemployment mixed with mental health distress. 24 Furthermore, mental health problems in young adults influence long-term health and psychosocial functioning as well as general well-being. 25 In recent years, economic crises have become more frequent, albeit shorter-lived.…”
Section: Graduates In the Hostile Labour Market: Visible And Invisibl...mentioning
confidence: 99%
“…At a social level, civil unrest and increment of crime rates can occur as major drawbacks of unemployment. Furthermore, Cockshott et al (2021) investigated the experiences of unemployed UK university graduates with mental health issues by using Interpretative Phenomenological Analysis. The loss of expectation and disorientation, a sense of waste and failure because of unemployment, stigma and shame were major issues that affected the mentality of unemployed graduates in this study and Cockshott et al (2021) suggested to have counselling services in universities that can better manage the transition to the employment of graduates.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cockshott et al (2021) investigated the experiences of unemployed UK university graduates with mental health issues by using Interpretative Phenomenological Analysis. The loss of expectation and disorientation, a sense of waste and failure because of unemployment, stigma and shame were major issues that affected the mentality of unemployed graduates in this study and Cockshott et al (2021) suggested to have counselling services in universities that can better manage the transition to the employment of graduates. In addition to this, Khezri et al (2020) claimed that, unemployed graduates' became anti-social due to the influence of unemployment and it is considered a threat to social and political development.…”
Section: Introductionmentioning
confidence: 99%